Současné možnosti měření nitroočního tlaku - Hornová, J; Baxant, A (Ceska a slovenska oftalmologie, 2013)
Authors introduced current possibilities of measuring intraocular pressure (IOP). A list of available methods of monitoring IOP is published; contact measurement method IOP directly on the cornea, but also over upper lid, methodology of minimal contact and non-contact measurement. Following contact methods are described; former measurements of IOP by impression Schiotz tonometer and the current methodology applanation. So far as the gold standard measurement Goldmann applanation tonometer (GAT) is considered, another methodology with applanation measurements are compared: Pascal dynamic contoured tonometer (DCT ), BioResonator - resonant applanation tonometer (ART ), digital applanation tonometer Tonopen and last hit: continuous measurement of IOP by Sensimed Triggerfish. Orientation and rapid assessment is palpation pressure control over the lid and measuring by tonometer Diaton. Rebound tonometer (RBT) iCare belongs to measurements with minimal contact, no need anesthetic drops and fluorescein, therefore a self - home version of IOP measurements (Icare ONE) is developed. Non-contact measurement of IOP by different pneumotonometers is popular for screening assessment of IOP. Reichert Ocular Response Analyzer (ORA) is a non-contact applanation IOP measurement and reveals additional properties of the cornea. In the discussion of a range methodology is evaluated, the experience of other authors and their own experience is compared. For monitoring of patients is necessary to select the most suitable methodology, measure repeatedly and accurately to allow long-term monitoring of intraocular pressure.
Keywords: Intraocular Pressure; nitrooční tlak; Reproducibility of Results; Ocular Hypertension; glaukom; oční hypertenze; Humans; reprodukovatelnost výsledků; tonometrie oční; Glaucoma; Tonometry, Ocular; lidé